Comparison of Micro-Percutaneous and Mini-Percutaneous Nephrolithotomy in the Treatment of Renal Stones: A Systematic Review and Meta-Analysis - Gao, Xiaoshuai; Wang, Wei; Peng, Liao; Di, Xingpeng; Xiao, Kaiwen; Chen, Jixiang; Jin, Tao (Frontiers in Surgery, 2021)
Background: To assess the efficacy and safety of micro-percutaneous nephrolithotomy (Microperc) and mini-percutaneous nephrolithotomy (Miniperc) in the treatment of moderately sized renal stones. Methods: Literature search of PubMed, Web of Science, and Embase was performed prior to January 2021. We used odds ratios (OR) and weighted mean difference (WMD) for dichotomous variables and continuous variables, respectively. Results were pooled using Review Manager version 5.3 software. Results: A total of six studies involving 291 Microperc and 328 Miniperc cases was included. The overall stone-free rate (SFR) of Microperc was 87.29% (254/291), while the SFR of Miniperc was 86.59% (284/328). Microperc was associated with lower hemoglobin drop (WMD: −0.98; P = 0.03) and higher renal colic requiring D-J stent insertion (OR: 3.49; P = 0.01). No significant differences existed between Microperc and Miniperc with respect to SFR (OR: 1.10; P = 0.69), urinary tract infection (OR: 0.38; P = 0.18), operative time (WMD: −5.76; P = 0.62), and hospital stay time (WMD: −1.04; P = 0.07). Conclusions: Our meta-analysis demonstrated that Microperc could produce an SFR that was comparable with that of Miniperc. Microperc was associated with lower hemoglobin drop, while Miniperc was associated with lower renal colic rates. In addition, the operation time and hospital stay time for both these procedures were similar.